2019
DOI: 10.2344/anpr-65-04-05
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic Radiographic Relationship of the Mandibular Foramen to the Anterior Border of the Ramus and Occlusal Plane as an Aid in Inferior Alveolar Nerve Block

Abstract: The location of the mandibular foramen (MF) on digital panoramic radiographs can be an important guide for clinicians when administering the inferior alveolar nerve block (IANB) for dental anesthesia of the mandible. This study, aimed to assess the location of the MF relative to the anterior border (AB) of the ramus and the occlusal plane (OP) from digital panoramic radiographs. An observational case series study was conducted on digital panoramic radiographs from the oral and maxillofacial radiology departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…It needs to be combined with other graphics to produce a variety of vivid visual experience. There is also the most likely to cause strong attention to the movement factor, is one of the spatial processing techniques [21].…”
Section: Advantages Of Vr Technology In the Bluish-white Porcelain Display Design Of Fanchang Kilnmentioning
confidence: 99%
“…It needs to be combined with other graphics to produce a variety of vivid visual experience. There is also the most likely to cause strong attention to the movement factor, is one of the spatial processing techniques [21].…”
Section: Advantages Of Vr Technology In the Bluish-white Porcelain Display Design Of Fanchang Kilnmentioning
confidence: 99%
“…[ 15 ] The results of our study are in agreement with those of the literature where no significant differences in MF location between the gender,[ 4 21 ] and also between the right and left sides of the mandible, were noted. [ 18 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to that seen in previous studies,[ 7 18 23 ] whereas few other authors have reported contradictory results. [ 4 10 22 24 ] Ezoddini Ardakani et al . in a study on Iranian children reported that the MF was located below the OP at age 9 years and was slightly below or above the OP in those aged above 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular foramen (MF) is the channel where the inferior alveolar nerve (IAN) and vessels pass through to supply the mandible, mandibular teeth and the lower lips with nutrition and sensory perception [1]. The exact localization of MF would decrease failure rates of IANB, as IAN should be anesthetized before entering MF to increase the success rate of IANB [2][3][4]. Moreover, the location of MF is crucial in planning various mandibular surgeries such as bilateral sagittal split osteotomy to avoid injury of the inferior alveolar bundle.…”
Section: Introductionmentioning
confidence: 99%
“…Interoperative complications include pain during dental procedures and hemorrhage due to injury of inferior alveolar vessels. Postoperative complications comprise hematoma, trismus, fracture of mandible and permanent loss of sensation in mandibular area that may reach morbidity due to injury of inferior alveolar nerves and vessels [2][3][4]. It is reported that the location of MF is affected by age, sex, loss of teeth and ethnicity [2,6,7].…”
Section: Introductionmentioning
confidence: 99%